2010
DOI: 10.4149/neo_2010_01_062
|View full text |Cite
|
Sign up to set email alerts
|

Expression and its clinical significance of heat shock protein gp96 in human osteosarcoma

Abstract: The aim of the study was to observe the expression of heat shock protein gp96 (HSPgp96) and explore its clinical significance in human osteosarcoma.The expression of HSPgp96 was studied in 44 osteosarcoma tissues including 24 osteoblastic sarcoma and 20 chondroblastic sarcoma, normal tissues adjacent to the sarcomas were evaluated simultaneously.The immunoreactivity was found positive in all osteosarcoma tissues (44/44), but 21.5% (9/44) in normal tissues. HSPgp96 was mainly expressed in cytoplasm of osteoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…6E , Fig. S6A, B , both super-resolution immunofluorescence imaging and analysis of subcellular fractions showed that gp96 is mainly localized in the ER, and a small fraction of gp96 also exists in the cytosol and nucleus, which was consistent to previous studies 34 , 35 . While Eomes and Trim28 mainly exist within the nucleus, small amounts of them were found to be distributed in the cytosol.…”
Section: Resultssupporting
confidence: 91%
“…6E , Fig. S6A, B , both super-resolution immunofluorescence imaging and analysis of subcellular fractions showed that gp96 is mainly localized in the ER, and a small fraction of gp96 also exists in the cytosol and nucleus, which was consistent to previous studies 34 , 35 . While Eomes and Trim28 mainly exist within the nucleus, small amounts of them were found to be distributed in the cytosol.…”
Section: Resultssupporting
confidence: 91%
“…It is also consistent with recent studies of esophageal squamous cell carcinomas [22], primary lung cancer [23] and osteosarcoma [24], which showed a correlation between Gp96 expression and prognosis of those carcinomas, suggesting that tumors with high Gp96 expression are very likely to recur and have a poor prognosis. However, the mechanism by which Gp96 expression contributes to tumor progression of NPC remains to be elucidated.…”
Section: Discussionsupporting
confidence: 80%
“…HSPgp96, was mainly expressed in the cytoplasm of osteoblastic sarcoma with less differentiation. The authors affirm that the HSPgp96 has a role in the pathogenesis of bone tumor, but the marker cannot be used in determining the degree of malignancy and as a target for tumor immunity (Guo et al, 2010). …”
Section: Osteosarcomamentioning
confidence: 99%
“…Guo et al (2010) assesses the role of heat shock protein gp96 (HSPgp96) in human osteosarcoma. HSPgp96, was mainly expressed in the cytoplasm of osteoblastic sarcoma with less differentiation.…”
Section: Osteosarcomamentioning
confidence: 99%